A new species of Cyrtodactylus (Squamata: Gekkonidae) from Vientiane Province, northern Laos - Sitthivong, Saly; Luu, Vinh Quang; Ha, Ngoan Van; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2019)
A new species of the genus Cyrtodactylus from Vientiane Province, northern Laos is described based on morphological and molecular data. Cyrtodactylus muangfuangensis sp. nov. can be distinguished from remaining congeners by the following combination of characters: maximum SVL 83.9 mm; dorsal pattern consisting of dark nuchal loop, nape band and five dark transversal bands between limb insertions; intersupranasals two; dorsal tubercles present on occiput, body, hind limbs and tail base; 15 or 16 irregular dorsal tubercle rows at midbody; lateral folds clearly defined, without interspersed tubercles; 31–37 ventral scales between ventrolateral folds; six precloacal pores and 15 femoral pores in males, which are interrupted by six to eight poreless scales; six precloacal pitted scales plus in total 10–15 pitted femoral scales in females, which are separated by six to eight poreless scales; enlarged precloacal and femoral scales present; two or three postcloacal tubercles; median subcaudal scales transversely enlarged. In molecular analyses, the new species is strongly supported as a member of the Cyrtodactylus phongnhakebangensis species group, and weakly corroborated as a sister taxon to C. pageli. Pairwise genetic comparison shows that it is at least 18% divergent from other congeners in the species group based on a fragment of the mitochondrial cytochrome C oxidase subunit I gene.